2019
DOI: 10.1155/2019/3215219
|View full text |Cite
|
Sign up to set email alerts
|

Research on Construction Safety Risk Assessment of New Subway Station Close‐Attached Undercrossing the Existing Operating Station

Abstract: With the large-scale construction of urban rail transit, it will lead to the intersection and transfer of various lines, resulting in more transfer stations. The transfer station is a collection point for multiple subway lines, which is difficult to construct and has a high construction risk. The construction of the new subway station and the operation of the existing subway station are mutually influenced during the close-attached undercrossing construction. Considering the two objectives of ensuring the smoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…e term of "coupling" is originated from physics and is a phenomenon in which two or more systems or forms of motion interact with each other [20]. e risk coupling of the subway shield tunnel refers to the dependence degree of individual risk occurrence on the occurrence of other risks, and the degree of influence on other risks, the greater the dependence degree among risks, the greater the degree of coupling [21]. e calculation of system coupling degree can be realized by the N-K model, the coupling degree model, the interpretative structural model, and the nonlinear dynamic model.…”
Section: Coupling Mechanismmentioning
confidence: 99%
“…e term of "coupling" is originated from physics and is a phenomenon in which two or more systems or forms of motion interact with each other [20]. e risk coupling of the subway shield tunnel refers to the dependence degree of individual risk occurrence on the occurrence of other risks, and the degree of influence on other risks, the greater the dependence degree among risks, the greater the degree of coupling [21]. e calculation of system coupling degree can be realized by the N-K model, the coupling degree model, the interpretative structural model, and the nonlinear dynamic model.…”
Section: Coupling Mechanismmentioning
confidence: 99%
“…Many scholars have carried out a great deal of research work on urban safe construction and green construction [1][2][3]. A lot of scholars have carried out the related research work on subway safety construction [4][5][6]. As an underground linear project, the subway will intersect or underpass other projects in the construction process.…”
Section: Introductionmentioning
confidence: 99%
“…In that paper, environmental risk was a part of safety risk. Luo et al [9] developed a safety risk assessment model using the analytic hierarchy process (AHP) and fuzzy matter-element method (FMEM). To the best of the authors' knowledge, no research has been reported to date on environmental risk assessment of subway station construction.…”
Section: Introductionmentioning
confidence: 99%
“…e choice of risk assessment model is another crucial task in the environmental risk assessment of metro station construction projects. Luo et al [9] used the FMEM to calculate the correlation between the geo-environmental risk indicators and classify the risk level of the indicators to determine the project's risk level. Since it is difficult to obtain accurate engineering data in construction engineering, Wang & Chen [20] proposed a systematic decision support method based on a fuzzy integrated Bayesian network (FCBN), which combines the fuzzy integrated evaluation method (FCEM) and Bayesian network (BN), to analyze the safety risk of subway construction projects under uncertain conditions.…”
Section: Introductionmentioning
confidence: 99%